Shunted Hydrocephalus Has a Significant Impact on Quality of Life in Children With Spina Bifida. Issue 10 (22nd May 2013) - Ramachandra, Puneeta; Palazzi, Kerrin L.; Skalsky, Andrew J.; Marietti, Sarah; Chiang, George
Abstract : Objective: To determine which clinical (health status) and nonclinical (demographic) factors may affect perceptions of quality of life in children with spina bifida and their parents. Design: A prospective study by using a validated questionnaire. Setting: A multidisciplinary spina bifida clinic at a pediatric tertiary referral center. Patients: Thirty‐three children with spina bifida aged 5‐18 years and 41 parents of children with spina bifida aged 2‐18 years completed questionnaires after informed consent was obtained. Methods: The Peds QL 4.0 Short Form 15 questionnaire was administered to children with spina bifida and their parents. Additional data were collected, including socioeconomic status, self‐reported ethnicity, insurance status, ambulatory status, presence of shunted hydrocephalus, and continence. All completed questionnaires were included in the final analysis. Results: Self‐reported physical and psychosocial health scores for patients in our study were lower than previously published scores from healthy children. Patients with a shunted hydrocephalus had significantly lower self‐reported physical health scores compared with those without shunted hydrocephalus (61.4 versus 39.3; P = .015). Self‐reported physical health score in those with shunted hydrocephalus improved with age (Spearman ρ = 0.42; P = .017). Shunted hydrocephalus remained significant on multivariate analysis. Ethnicity, insurance, socioeconomic status, ambulatory status, and urinary and fecal continence were not associated with self‐reported physical or psychosocial scores. Parent‐reported scores were not associated with any of the variables of interest. There was excellent correlation between parent‐reported and self‐reported psychosocial health scores (Spearman ρ = 0.636; P < .001) but not physical health scores (Spearman ρ = 0.023; P = .905). Conclusions: Shunted hydrocephalus has a negative impact on the perception of quality of life, an effect that may be attenuated by age. Further study and more‐specific measurement tools are needed to better understand health‐related quality of life in children with spina bifida.